Spontaneous emission activity of lithosphere and seismoelectromagnetic phenomena - Shuman, V. N. (Geofizicheskiy Zhurnal, 2016)
New ideas and approaches to describing spontaneous emission of lithosphere are being discussed — seismic, seismoacoustic and electromagnetic based on analysis of non-stationary processes and metastable conditions in active geomedium. It is accentuated that these emissions are not only a dynamic but also spatial-temporal chaos in distributed energy-saturated geo-systems. Attention is concentrated on a diffusion-relaxation component of lithospheric noise interpreted as a reflection of non-linear dynamics of non-equilibrium geomedium, a result of interaction and concordance between mechanisms of its self-organization, which determine the trends of evolutionary processes development and effects of dynamic relaxation, which reflect the role of fluctuation-dissipative factors. Essential role of criticality fronts in the processes of their generation is being noted, in particular, of percolation-diffusion ones and of related transitional processes in non-stationary geomedium, which are called transitional dispersion. It is considerable that spontaneous emissions as ordered spatial-temporal structures, which are determined by the properties of the geo-system, might be interpreted in terms of self-excited oscillations of relaxation type and, in particular, auto-structures.